The growth and early development of eggplant (Solanum melongena L.) seedlings as affected by the application of Effective Microorganisms (EM) - Tan, Si Li (Universiti Malaysia Sabah, 2017)
The uniqueness and the biosynthetic capabilities of the effective microorganism (EM) solution has been found effective under field condition as an inoculant to increase the microbial diversity of soil, improve the physical and chemical properties of soil, enhance plant nutrition as well as enhance plant growth. This research was conducted at rain shelter 9B of Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Mile 10, Sandakan to determine the growth and early development of eggplant (Solanum melongena L.) as affected by the application of EM. The experimental design was Completely Randomized Design (CRD) with five concentrations factor and six replications of each treatment. Five concentrations of EM dilutions namely 0 ml L·1 (control treatment), 20 ml L·1, 30 ml L·1, 40 ml L·1 and 50 ml L·1 were applied at 10, 20 and 30 days intervals through a foliar spray. Data on of plant height, stem diameter, leaf numbers, leaf length, leaf width, root fresh weight, root dry weight, leaf dry weight, shoot fresh weight, shoot dry weight, plant fresh weight, plant dry weight, chlorophyll content and shoot-root ratio of Solanum melongena seedlings were recorded six weeks after seed establishment. Results were analyzed using SPSS and the treatment means were compared by using Tukey test at 5% significant level. In this study, the best growth and early development were observed from eggplant seedlings under control treatment. The measurements also revealed that 40 ml L·1 of effective microorganisms dilution applied to the eggplants seedlings showed the highest plant growth among the treatment whereas plants treated with 20 ml L·1 of effective microorganisms dilution showed the least plant growth. Hence, EM will not be able to improve the growth and early development of eggplant seedlings. Further studies on the application of EM with other soil amendments are needed to estimate if EM is suitable for the growth of eggplant seedlings.